Doktor Kot, Doktor Sla – book doctors, plant doctors and the segmentation of the medical market place in Meghalaya, northeast India. Issue 2 (4th May 2019) - Albert, Sandra; Porter, John; Green, Judith
ABSTRACT: Despite decades of research on India's plural health care market, the practices of many local health traditions outside the allopathic and codified traditions are under-studied. Drawing on interview and observational data, this paper explores the space in which indigenous traditional Khasi healers in Meghalaya state, northeast India, practice. Khasi indigenous healers describe themselves as doktor sla, plant doctors, to distinguish themselves from doktor kot, or book doctors. This distinction operates as a rhetorical resource, utilised to carve a distinct sphere of expertise in relation to the allopathic sector, and to mark claims for the specifically local appropriateness of traditional practices within a shifting market of state-sponsored provision. Khasi healers are a heterogeneous group who treat a wide variety of conditions, including physical ailments which have no obvious correlates in biomedical systems, and musculoskeletal disorders, with which they have recognised expertise. In addition to claiming these discrete strengths, healers also present themselves as accommodating deficiencies in biomedicine, including inherent generic weaknesses of allopathic care as well as specific local gaps in rural health care provision. Thus, the expertise niches of traditional healers have evolved through their interactions with, and the needs of, the community, but also through managing a shifting boundary with biomedical practitioners, who are explicitly sceptical of their efficacy, but tacitly accepting of the ways in which they manage the gaps in biomedical provision. While codified non-biomedical traditions in India have engaged in universalising professionalising projects, in this setting at least, non-codified practitioners have instead utilised discourses of localism.